Correction to: Investigation of Liquefaction in Balaroa, Petobo, and Jonooge (Central Sulawesi, Indonesia) Caused by the 2018 Palu Earthquake Sequence - Triyono, Rahmat; Widiyantoro, Sri; Zulfakriza, Zulfakriza; Supendi, Pepen; Rahman, Aditya Setyo; Gunawan, Mohamad Taufik; Oktavia, Nur Hidayati; Rahmatullah, Fajri Syukur; Fadhilah, Fildzah Zaniati; Habibah, Nur Fani; Sativa, Oriza; Permana, Dadang; Wallansha, Robby; Octantyo, Ardian Yudhi; Persada, Yoga Dharma; Pranata, Bayu; Sujabar, Sujabar (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Correction to: Journal of Engineering and Technological Sciences https://doi.org/10.5614/j.eng.technol.sci.2024.56.3.1 The article titled